Peran Anggaran Dasar dan Rumah Tangga dalam Mewujudkan Gereja yang Tertib dan Bertumbuh - Ferdin Halawa; Marlince Diana Lende; Sebayanti Gamerakhai; Agra Pahala Nainggolan; Jonidius Illu (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the role of the Articles of Association and Bylaws (AD/ART) in realizing an orderly and growing church. The Church as a spiritual and social organization needs an orderly system to achieve its ministry goals effectively and sustainably. Through a qualitative-descriptive approach, data was collected through literature studies, observations, and interviews with leaders and congregation members in several local churches. The results of the study show that AD/ART plays a role as a structural guideline that regulates the duties, authorities, and responsibilities of the ministry, as well as as the foundation of ministry ethics that maintains integrity and order in the church body. In addition, AD/ART has also proven to be a strategic instrument in encouraging church growth through long-term planning, leadership regeneration, congregation participation, and accountable financial management. Consistent implementation of AD/ART creates organizational stability, strengthens the church's identity, and increases the trust and involvement of congregation members. Thus, AD/ART is a crucial element in the construction of a healthy, orderly, and sustainable growing church.